Changes in Cytokine Levels and NK Cell Activation Associated with Influenza - Jost, Stephanie; Quillay, Heloise; Reardon, Jeff; Peterson, Eric; Simmons, Rachel P.; Parry, Blair A.; Bryant, Nancy N. P.; Binder, William D.; Altfeld, Marcus (PloS one, 2011)
Several studies have highlighted the important role played by murine natural killer (NK) cells in the control of influenza infection. However, human NK cell responses in acute influenza infection, including infection with the 2009 pandemic H1N1 influenza virus, are poorly documented. Here, we examined changes in NK cell phenotype and function and plasma cytokine levels associated with influenza infection and vaccination. We show that absolute numbers of peripheral blood NK cells, and particularly those of CD56(bright) NK cells, decreased upon acute influenza infection while this NK cell subset expanded following intramuscular influenza vaccination. NK cells exposed to influenza antigens were activated, with higher proportions of NK cells expressing CD69 in study subjects infected with seasonal influenza strains. Vaccination led to increased levels of CD25+ NK cells, and notably CD56(bright) CD25+ NK cells, whereas decreased amounts of this subset were present in the peripheral blood of influenza infected individuals, and predominantly in study subjects infected with the 2009 pandemic H1N1 influenza virus. Finally, acute influenza infection was associated with low plasma concentrations of inflammatory cytokines, including IFN-γ, MIP-1β, IL-2 and IL-15, and high levels of the anti-inflammatory cytokines IL-10 and IL-1ra. Altogether, these data suggest a role for the CD56(bright) NK cell subset in the response to influenza, potentially involving their recruitment to infected tissues and a local production and/or uptake of inflammatory cytokines.